Hypoxia induces polycystin-1 expression in the renal epithelium - Grampp, Steffen; Kraus, Andre; Skoczynski, Kathrin; Schiffer, Mario; Krüger, René; Naas, Stephanie; Schödel, Johannes; Buchholz, Björn (Royal Society Open Science, 2023)
Mutations in polycystin-1 which is encoded by the PKD1 gene are the main causes for the development of autosomal dominant polycystic kidney disease. However, only little is known about the physiological function of polycystin-1 and even less about the regulation of its expression. Here, we show that expression of PKD1 is induced by hypoxia and compounds that stabilize the hypoxia-inducible transcription factor (HIF) 1α in primary human tubular epithelial cells. Knockdown of HIF subunits confirms HIF-1α-dependent regulation of polycystin-1 expression. Furthermore, HIF ChIP-seq reveals that HIF interacts with a regulatory DNA element within the PKD1 gene in renal tubule-derived cells. HIF-dependent expression of polycystin-1 can also be demonstrated in vivo in kidneys of mice treated with substances that stabilize HIF. Polycystin-1 and HIF-1α have been shown to promote epithelial branching during kidney development. In line with these findings, we show that expression of polycystin-1 within mouse embryonic ureteric bud branches is regulated by HIF. Our finding links expression of one of the main regulators of accurate renal development with the hypoxia signalling pathway and provides additional insight into the pathophysiology of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-06-30
Keywords: hypoxia; hypoxia-inducible factor; kidney development; PKD1; polycystic kidney disease; transcription regulation

Loss of Polycystin-1 causes cAMP-dependent switch from tubule to cyst formation. - Scholz, Julia; Kraus, Andre; Lueder, Dominik; Skoczynski, Kathrin; Schiffer, Mario; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (iScience, 2022)
Autosomal dominant polycystic kidney disease is the most common monogenic disease that causes end-stage renal failure. It primarily results from mutations in the PKD1 gene that encodes for Polycystin-1. How loss of Polycystin-1 translates into bilateral renal cyst development is mostly unknown. cAMP is significantly involved in cyst enlargement but its role in cyst initiation has remained elusive. Deletion of Polycystin-1 in collecting duct cells resulted in a switch from tubule to cyst formation and was accompanied by an increase in cAMP. Pharmacological elevation of cAMP in Polycystin-1-competent cells caused cyst formation, impaired plasticity, nondirectional migration, and mis-orientation, and thus strongly resembled the phenotype of Polycystin-1-deficient cells. Mis-orientation of developing tubule cells in metanephric kidneys upon loss of Polycystin-1 was phenocopied by pharmacological increase of cAMP in wildtype kidneys. In vitro, cAMP impaired tubule formation after capillary-induced injury which was further impaired by loss Polycystin-1.
EVALuna2:505609

P2Y2R and Cyst Growth in Polycystic Kidney Disease. - Kraus, Andre; Skoczynski, Kathrin; Brötsch, Martin; Burzlaff, Nicolai; Leipziger, Jens; Schiffer, Mario; Büttner-Herold, Maike; Buchholz, Björn (Journal of the American Society of Nephrology, 2024)
EVALuna2:569374

The chloride channel CFTR is not required for cyst growth in an ADPKD mouse model - Talbi, Khaoula; Cabrita, Inês; Kraus, Andre; Hofmann, Sascha; Skoczynski, Kathrin; Kunzelmann, Karl; Buchholz, Björn; Schreiber, Rainer (The FASEB Journal, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the development of bilateral renal cysts which enlarge continuously, leading to compression of adjacent intact nephrons. The growing cysts lead to a progressive decline in renal function. Cyst growth is driven by enhanced cell proliferation and chloride secretion into the cyst lumen. Chloride secretion is believed to occur mainly by the cAMP-activated cystic fibrosis transmembrane conductance regulator (CFTR), with some contribution by the calcium-activated chloride channel TMEM16A. However, our previous work suggested TMEM16A as a major factor for renal cyst formation. The contribution of CFTR to cyst formation has never been demonstrated in an adult ADPKD mouse model. We used mice with an inducible tubule-specific Pkd1 knockout, which consistently develop polycystic kidneys upon deletion of Pkd1. Cellular properties, ion currents, and cyst development in these mice were compared with that of mice carrying a co-deletion of Pkd1 and Cftr. Knockout of Cftr did not reveal any significant impact on cyst formation in the ADPKD mouse model. Furthermore, knockout of Cftr did not attenuate the largely augmented cell proliferation observed in Pkd1 knockout kidneys. Patch clamp analysis on primary renal epithelial cells lacking expression of Pkd1 indicated an only marginal contribution of CFTR to whole cell Cl− currents, which were clearly dominated by calcium-activated TMEM16A currents. In conclusion, CFTR does not essentially contribute to renal cyst formation in mice caused by deletion of Pkd1. Enhanced cell proliferation and chloride secretion is caused primarily by upregulation of the calcium-activated chloride channel TMEM16A.
CRIS-Team Scopus Importer:2021-10-08
Keywords: ADPKD; CFTR; cyst growth; proliferation; TMEM16A

The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number